THE EFFECTIVENESS OF TEAM ASSISTED INDIVIDUALIZATION LEARNING MODEL WITH REALISTIC MATHEMATICS APPROACH ON MATHEMATICAL PROBLEM-SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Winda Nur Akhadya; Ariyadi Wijaya (Jurnal Pedagogi Matematika, 2017)
This  study  aims  to  determine  the  effectiveness of  Team  Assisted  Individualization learning  model  with realistic  mathematics  approach  on  mathematical  problem-solving  ability of  Junior  High  School  students.  This research is quasi experiment with pretest posttest control group design. The subjects are 64 students from 3 Godean Junior High School which consist of class VIII F as the experimental class using Team Assisted Individualization learning model with realistic mathematics approach and class VIII D as the control class using expository learning model with deductive approach. Instrument that used are learning observation sheet and pretest-posttest items of mathematical problem-solving ability. Based on this research, it is conclude that Team Assisted Individualization learning model with realistic mathematics approach effective to the mathematical problem-solving ability of junior high  school  students. Furthermore Team  Assisted  Individualization learning  model with  realistic  mathematics approach is more effective than expository learning model with deductive approach to the mathematical problemsolving ability of Junior High School students.